2007
DOI: 10.1007/s10494-007-9091-5
|View full text |Cite
|
Sign up to set email alerts
|

Simulations of Turbulent Flow in a Plane Asymmetric Diffuser

Abstract: Large-eddy simulations (LES) of a planar, asymmetric diffuser flow have been performed. The diverging angle of the inclined wall of the diffuser is chosen as 8.5 • , a case for which recent experimental data are available. Reasonable agreement between the LES and the experiments is obtained. The numerical method is further validated for diffuser flow with the diffuser wall inclined at a diverging angle of 10 • , which has served as a test case for a number of experimental as well as numerical studies in the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…It is important to note that the method described here represents an improvement with respect to the so-called recycling techniques (see for instance the work by Lund et al [38]), since the auxiliary simulation provides a sufficiently long time history of the inflow so that any unphysical behaviour due to an artificial recycling frequency is avoided. In addition to this, the boundary-layer and the main cylinder simulations are not coupled, and therefore no spatial correlations or artificial frequencies will appear (Herbst et al [39]). …”
Section: Numerical Representation Of the Experimental Set-upmentioning
confidence: 99%
“…It is important to note that the method described here represents an improvement with respect to the so-called recycling techniques (see for instance the work by Lund et al [38]), since the auxiliary simulation provides a sufficiently long time history of the inflow so that any unphysical behaviour due to an artificial recycling frequency is avoided. In addition to this, the boundary-layer and the main cylinder simulations are not coupled, and therefore no spatial correlations or artificial frequencies will appear (Herbst et al [39]). …”
Section: Numerical Representation Of the Experimental Set-upmentioning
confidence: 99%
“…Azad used pulsed-wire skin friction probes to show that the friction velocity consistently decreased along the diffuser. However, since the mean flow detached a very short distance from the diffuser throat [1,13], the present simulation indicated that the distribution inevitably decreased at the location. The rapid decrease in the skin friction also leads to decrease in the friction Reynolds number or Kármán number, defined as Re τ (x) = u τ (x)R(x)/ν (not shown).…”
Section: Mean Propertiesmentioning
confidence: 62%
“…The near-wall streaky structures in the asymmetric planar diffuser were described by Herbst et al [1]. They reported that the structures near the inclined wall became wider as the flow propagated.…”
Section: Instantaneous Flow Fieldsmentioning
confidence: 77%
See 2 more Smart Citations